ANALISIS SIKAP ILMIAH SISWA BERDASARKAN KURIKULUM 2013 PADA PEMBELAJARAN IPA KELAS VII DI SMP NEGERI 13 PEKANBARU - Cici Eka Aryanti; Hendar Sudrajad; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The study was aimed to describe students' scientific attitudes on science learning in class VII. This study was conducted at SMP Negeri 13 Pekanbaru in April 2018 to December 2018. The subjects in this study was seventh grade students of Pekanbaru Public Middle School 13 semester 2017/2018 academic year. The type of research used was descriptive research with survey methods, types of content analysis or documents. The data analysis technique used was descriptive analysis. The results of the data analysis showed students’scientific attitude in sufficient categories with a percentage of 57.14%, in the good category of 28.57% and in the excellent category 14.28%, while for the 2nd meeting scientific attitudes of students in the good category amounted to 85.71% and the category was very good amounting to 14.28%, overall the scientific attitudes of students in first meeting with an average score of 2.2 in the category which increased enough at the 2nd meeting with a score of 2.8 in the good category. Based on data analysis it can be concluded that overall the scientific attitude of students in science learning is in a good category.Key Words: Science Learning, Scientific Approach, Scientific Attitude